The Business of News in England, 1760-1820 - Gardner, Victoria E. M.; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
The Business of News in England, 1760-1820 explores the commerce of the English press during a critical period of press politicization, as the nation confronted foreign wars and revolutions that disrupted domestic governance.
Keywords: Civilization-History.; Great Britain-History.; Economic history; History, Modern; Social history; Industries